2023
DOI: 10.1002/mbo3.1350
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient export of a disulfide‐bonded protein to the periplasm and medium by the Tat pathway using CyDisCo in Escherichia coli

Abstract: High‐value heterologous proteins produced in Escherichia coli that contain disulfide bonds are almost invariably targeted to the periplasm via the Sec pathway as it, among other advantages, enables disulfide bond formation and simplifies downstream processing. However, the Sec system cannot transport complex or rapidly folding proteins, as it only transports proteins in an unfolded state. The Tat system also transports proteins to the periplasm, and it has significant potential as an alternative means of recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Alternatively, the TAT pathway, another well-characterized secretion pathway, provides a fascinating alternative for protein secretion when proper folding occurred within the cytoplasm prior to secretion (Berks, 2015 ). Proteins such as GFP (Albiniak et al., 2013 ), protein glutaminase (Niu et al., 2019 ), disulfide bond‐containing protein (Arauzo-Aguilera et al., 2023 ), and laccases (Valimets et al., 2023 ) have been successfully secreted using the TAT pathway. Next, we will consider the possibility of NpAS being targeted for export via the TAT pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, the TAT pathway, another well-characterized secretion pathway, provides a fascinating alternative for protein secretion when proper folding occurred within the cytoplasm prior to secretion (Berks, 2015 ). Proteins such as GFP (Albiniak et al., 2013 ), protein glutaminase (Niu et al., 2019 ), disulfide bond‐containing protein (Arauzo-Aguilera et al., 2023 ), and laccases (Valimets et al., 2023 ) have been successfully secreted using the TAT pathway. Next, we will consider the possibility of NpAS being targeted for export via the TAT pathway.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, as one of the integral membrane proteins of Tat translocase, the expression of Sec-independent translocase protein TatA was differentially up-regulated (Figure S1 ) and enriched in the pathway of protein export and bacterial secretion. Arauzo-Aguilera et al (2023) reported recently protein YebF could be exported to the periplasm at high level through Tat pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, as one of the integral membrane proteins of Tat translocase, the expression of Sec-independent translocase protein TatA was differentially up-regulated ( Supplementary Figure S2 ) and enriched in the pathway of protein export and bacterial secretion. Arauzo-Aguilera et al ( 2023 ) reported recently protein YebF could be exported to the periplasm at high level through Tat pathway.…”
Section: Discussionmentioning
confidence: 99%